Analisis Yuridis Penegakan Hukum Terhadap Aparatur Sipil Negara Yang Terlibat Korupsi - Syakirah Farah Diva; Anza Ronaza Bangun (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Cases of corruption in Indonesia are still high and very common, Civil Servants (PNS) are the main element of the State Civil Apparatus (ASN) that plays a role in carrying out public service functions, governance, and national development. This strategic position requires PNS to have integrity, professionalism, and be free from corruption, collusion, and nepotism. However, the phenomenon of PNS involvement in criminal acts of corruption still occurs, which has implications for declining public trust in the government. Efforts to eradicate corruption against PNS are not only carried out through criminal law enforcement, but also through administrative personnel mechanisms as a form of internal bureaucratic oversight. The legal framework regarding sanctions against corrupt PNS is regulated in Law Number 5 of 2014 concerning ASN and its derivative regulations, which stipulate dishonorable dismissal as an administrative consequence for PNS found guilty of corruption. This study confirms that the double-track sanction system is an important instrument for creating a clean bureaucracy, but its effectiveness is highly dependent on the consistency of implementation, the commitment of civil service development officials, and an anti-corruption culture within the government.